Controlling oscillation amplitudes via feedback - Berns, Daniel Walther (2000)
This paper studies feedback control of limit cycle amplitudes in nonlinear systems. A graphical approach to bifurcation control is first briefly introduced, followed by the derivation of a nonlinear control law. Then, a suitable implementation of the design is developed via an approximation of the time-derivative term in the nonlinear state feedback controller. A classical model is finally simulated for illustration of the proposed control method.